FRI0707-HPR IS A TAILORED DELIVERY OF NORDIC WALKING ACCEPTABLE FOR PEOPLE WITH INFLAMMATORY RHEUMATIC DISEASE?. (June 2019) - Domaille, Melissa; Whybrow, Paul; Carver-Richardson, Elizabeth; Dures, Emma; Greenwood, Rosemary; Richards, Pamela; Robson, Joanna; Stellinga, Robert; Cramp, Fiona
Abstract : Background: People with inflammatory rheumatic diseases find it more difficult to stay physically active. Although interventions delivered in a clinical setting lead to short-term benefits, sustaining physical activity is challenging. Nordic Walking is a whole-body physical activity that involves walking with poles. It has been shown to be beneficial in long-term conditions but not specifically for inflammatory rheumatic diseases. Objectives: To establish the acceptability of a tailored Nordic Walking intervention in this population as preparation for a full efficacy trial. Methods: The intervention was developed collaboratively with patient research partners and involves a 30-minute training session followed by 10 one hour sessions of Nordic Walking over 10 weeks. Twelve people received the intervention between May and July 2018 and 12 more from September to November 2018. The intervention differed from standard Nordic Walking in several ways; initial training was provided in small groups of 2 to 3 by an instructor and a rheumatology physiotherapist. Flexible routes enabled participants to self-select their pace and distance. Routes radiated from, and circled back to, a central base with seats and drinking water. Participants completed a Short Form (36) Health Survey (the RAND) at baseline and post-intervention and took part in a focus group or interview. Results: Eighteen females and six males; mean age 60 years (range 35-82) were recruited from rheumatology clinics in the Southwest of England. All participants had a diagnosis of an inflammatory rheumatic disease including rheumatoid arthritis, psoriatic arthritis, axial spondyloarthropathy, connective tissue disease and systemic vasculitis. SF-36 data suggested a trend towards improvements and qualitative data provided insights into why the intervention was acceptable. All 24 participants enjoyed being active outdoors and reported benefits such as 'walking taller', 'better posture', 'better balance' and 'improved well-being'. Results reveal how important the adaptations with this tailored delivery of Nordic Walking were to participants. They found it reassuring that rheumatology specialists had contributed to the design of the intervention and that delivery was supported by a physiotherapist. Learning Nordic Walking in small groups alongside people with similar conditions was popular and meant that participants could walk at their own pace, engage with peers and felt supported. Participants said they would not join a non-specialised Nordic Walking group. Several participants subsequently purchased their own Nordic Walking poles and have arranged to meet independently to continue, indicating the potential for sustainability. Conclusion: This tailored delivery of Nordic Walking has the potential to offer acceptable, beneficial and sustainable physical activity for patients with inflammatory rheumatic diseases. Further research is now needed to investigate the long-term impact in a full efficacy trial. References: [1] Breyer M-K, Breyer-Kohansal R, et al. (2010) "Nordic Walking improves daily physical activities in COPD: A Randomised Controlled Trial"Respiratory Research; 11, 112 [2] Hutton I, GambleG, et al. (2010) "What is Associated with being Active in Arthritis? Analysis from the Obstacles to Action Study" Intern Med Journal; 40, 512-20 [3] O'Donovan RandKennedy N (2015) "Four legs instead of two – Perspectives on a Nordic Walking-Based Programme Among People with Arthritis"Disability and Rehabilitation; 37:18, 1635-1642 Disclosure of Interests: Melissa Domaille: None declared, Paul Whybrow: None declared, Elizabeth Carver-Richardson: None declared, Emma Dures Grant/research support from: Has previously received an independent learning grant from Pfizer, however the work has been completed and the grant has been closed., Rosemary Greenwood: None declared, Pamela Richards: None declared, Joanna Robson: None declared, Robert Stellinga: None declared, Fiona Cramp: None declared